2017
DOI: 10.1021/acsami.7b05253
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Phenotypically Distinct Cancer Cells Using Nanoparticle-Mediated Sorting

Abstract: Isolating subpopulations of heterogeneous cancer cells is an important capability for the meaningful characterization of circulating tumor cells at different stages of tumor progression and during the epithelial-to-mesenchymal transition. Here, we present a microfluidic device that can separate phenotypically distinct subpopulations of cancer cells. Magnetic nanoparticles coated with antibodies against the epithelial cell adhesion molecule (EpCAM) are used to separate breast cancer cells in the microfluidic pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 55 publications
0
44
0
Order By: Relevance
“…Noteworthy, more recently, the same group published other studies where they showed that cells with low EpCAM expression were related with disease progression since they presented higher collagen uptake and higher metabolic activity, for so, a more invasive behaviour, than cells with higher EpCAM expression ( Figure 3, B). 45 As well, they showed that patients were less responsive to therapy presented low EpCAM expression and high levels of cancer biomarkers, such as androgen receptor variant 7 (ARV7) and the mesenchymal marker, Ncadherin. 46 Despite the advance achieved in CTCs capture by using magnetic approaches, some issues still need to be addressed, such as nanoparticle aggregation, and consequently, cell aggregation.…”
Section: Epcam-based Strategiesmentioning
confidence: 98%
“…Noteworthy, more recently, the same group published other studies where they showed that cells with low EpCAM expression were related with disease progression since they presented higher collagen uptake and higher metabolic activity, for so, a more invasive behaviour, than cells with higher EpCAM expression ( Figure 3, B). 45 As well, they showed that patients were less responsive to therapy presented low EpCAM expression and high levels of cancer biomarkers, such as androgen receptor variant 7 (ARV7) and the mesenchymal marker, Ncadherin. 46 Despite the advance achieved in CTCs capture by using magnetic approaches, some issues still need to be addressed, such as nanoparticle aggregation, and consequently, cell aggregation.…”
Section: Epcam-based Strategiesmentioning
confidence: 98%
“…Huang et al designed a microfluidic microwell device that allows for immunomagnetic single-cell trapping for further cellular analysis at a single-cell level [238]. Green et al described a microfluidic magnetic sorting device that allows for the effective capturing of CTCs and dividing them into subpopulations according to levels of protein surface expression [248]. The analysis of subpopulations of CTCs that exhibit different biochemical and functional phenotypes may be useful to figure out if the CTCs acquire the metastatic potential by undergoing the epithelial-to-mesenchymal transition (EMT).…”
Section: Magnetic Cell Separationmentioning
confidence: 99%
“…Second-gen MagRC Number of zones/outlets 1 zone 1 4 zones 2, 3 6 zones 4 20 zones 5 8 zones 6, 7 10 zones 8 100 zones 9 3 outlets 10…”
Section: First-gen Magrcmentioning
confidence: 99%